Kualitas Hidup Mahasiswa Penghafal Al-Qur'an - Fajriyah, Arifatul Choiri; Mildaeni, Itsna Nurrahma; Hamzah, Imam Faisal; Wulandari, Dyah Astorini (Universitas Muhammadiyah Purwokerto, 2024)
Students who memorize the Qur'an and reside in an Islamic boarding school carry significant responsibilities and face considerable burdens due to numerous tasks and duties within the campus and its environment. These challenges can impact their overall well-being. This study aims to depict the quality of life experienced by students who memorize the Qur'an at Darussalam Islamic Boarding School in Dukuhwaluh Purwokerto. Using in-depth interviews based on WHOQoL-BREF criteria, the research explores dimensions such as physical health, psychological well-being, social interactions, and living conditions. Four student participants were involved in this study. Data analysis employed descriptive phenomenological techniques. The findings indicate that memorizing the Qur'an holds profound personal significance for each participant, notably contributing to an enhanced quality of life. This is attributed to their positive self-acceptance across physical, psychological, social, and environmental aspects.